Reform of the supervision over banks in the European Union – banking union - Zielińska, Klaudia (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article describes the concept of creating a banking union. It analyses the structure of each of its pillars as well as their evolution during the negotiations amongst Member States. The author also describes the attitude of Poland towards the project of a banking union.